2017
DOI: 10.18551/rjoas.2017-09.08
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effects of Economic Growth, Investment, Regional Taxes, and Capital Expenditure Toward the Income Disparity in Indonesia (2007-2013)

Abstract: This research is aimed to examine the effects of economic growth, Foreign Direct Investment, regional taxes, and provincial regional capital expenditure toward the income disparity in Indonesia from 2007-2013. This research utilized panel data composed from 33 provinces in Indonesia from 2007-2013 (231 observations). The method used in this research was regression analysis of panel data using Fixed Effect Model. Research results showed that economic growth and regional taxes had a positive influence toward the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…However, the factual income disparity shows that the owner of large capital in Indonesia is 1:10, in this condition the regulation of the government's side of the grassroots community and in general must be formulated seriously. However the foreign investment has been confirmed there is no implication in income disparity (Hardanto, Ismail, and Khusaini 2017).…”
Section: Bri and Economic Equitymentioning
confidence: 99%
“…However, the factual income disparity shows that the owner of large capital in Indonesia is 1:10, in this condition the regulation of the government's side of the grassroots community and in general must be formulated seriously. However the foreign investment has been confirmed there is no implication in income disparity (Hardanto, Ismail, and Khusaini 2017).…”
Section: Bri and Economic Equitymentioning
confidence: 99%
“…They concluded that consumption taxes raised both income disparity and economic development at the end of the report. Hardanto et al (2017), looked at how economic development and taxes influence income inequality in Indonesia from 2007 to 2013. Regression analysis results exhibited affirmative outcomes of economic growth and regional taxes had on income inequality.…”
mentioning
confidence: 99%